Cardiac arrest caused by coronary occlusion during transcatheter aortic valve implantation: a unique cause - Xin Gao; Feifei Chen; Xiaoxiao Jiang; Na Chen; Jinqiu Liu; Yong Luan; Guang Yang; Da Yin; Ran Guo (ESC Heart Failure, 2023)
Abstract Coronary artery occlusion (CAO) is a rare but life‐threatening complication of transcatheter aortic valve implantation (TAVI). The mechanism of CAO is the displacement of the native calcified valve leaflet over the coronary ostium. Here, we report on a woman who experienced sudden cardiac arrest and abrupt CAO during TAVI, which was caused by two different original obstructions, a rupture of aortic plaque or a partial tear of the aortic intima blocking the upper 2/3 of the left main trunk (LMT) ostium, and the transcatheter heart valve (THV) blocking the lower 1/3 of the LMT ostium. She was eventually successfully treated with the chimney stenting technique. Aortography other than coronary angiography was used to ascertain CAO. In patients presenting with abrupt cardiac arrest or cardiogenic shock with LMT occlusion, there must be prompt identification, and the causes of CAO may be various and rare. The identification of CAO relies not only on CAG but also on aortography, especially if the locations and origins of obstructions are special. Supportive therapy with an attempt at percutaneous revascularization is necessary. Pre‐procedural assessment is crucial prior to TAVI interventions. In cases with high risk of CAO, upfront coronary artery protection can be provided.